Análise de competências espontâneas producente e pouco producente de aprendizes de língua inglesa - Santos, Ana Cecília Fernandez dos (Universidade Federal de São Carlos, 2018)
In the past few years, many undergraduate and graduate students from a federal university in the interior of São Paulo state said they used different procedures to study English outside the classroom. In 2015, we proposed students of the 1st year of the Letters Portuguese/English course to write how they had learned English. All the answers showed that they had studied through television series, music, movies, games and the internet. Regarding this, students’ learning strategies (PAIVA, 2005), competences (ALMEIDA FILHO, 2016) and beliefs (BARCELOS, 2004) were investigated. However, we believe that these elements are related to the Spontaneous Competence (ALMEIDA FILHO, 2014). Considering this, we intend to comprehend the characteristics of the productive Spontaneous Competence. This qualitative and exploratory research (SILVEIRA e CÓRDOVA, 2009; SELIGER e SHOHAMY, 1989) was developed with Library and Information Science undergraduate students from a federal university in the state of São Paulo. They answered a questionnaire; they wrote a narrative; they had been observed in their English for Specific Purposes class; and their activities were analyzed. The data showed that different levels/types of motivation, affectivity, informal knowledge, learning strategies, attitudes, actions and other elements contributed to characterize this kind of competence.
Analyses of productive and less productive spontaneous competences in english language learners
Keywords: Competência espontânea; Aprendizes; Língua inglesa; Spontaneous competence; Learners; English; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA